New dimensions in surgical training: immersive virtual reality laparoscopic simulation exhilarates surgical staff - Huber, Tobias; Paschold, Markus; Hansen, Christian; Wunderling, Tom; Lang, Hauke; Kneist, Werner (Surgical endoscopy, 2017)
Introduction Virtual reality (VR) and head mount displays (HMDs) have been advanced for multimedia and information technologies but have scarcely been used in surgical training. Motion sickness and individual psychological changes have been associated with VR. The goal was to observe first experiences and performance scores using a new combined highly immersive virtual reality (IVR) laparoscopy setup. Methods During the study, 10 members of the surgical department performed three tasks (fine dissection, peg transfer, and cholecystectomy) on a VR simulator. We then combined a VR HMD with the VR laparoscopic simulator and displayed the simulation on a 360° video of a laparoscopic operation to create an IVR laparoscopic simulation. The tasks were then repeated. Validated questionnaires on immersion and motion sickness were used for the study. Results Participants’ times for fine dissection were significantly longer during the IVR session (regular: 86.51 s [62.57 s; 119.62 s] vs. IVR: 112.35 s [82.08 s; 179.40 s]; p = 0.022). The cholecystectomy task had higher error rates during IVR. Motion sickness did not occur at any time for any participant. Participants experienced a high level of exhilaration, rarely thought about others in the room, and had a high impression of presence in the generated IVR world. Conclusion This is the first clinical and technical feasibility study using the full IVR laparoscopy setup combined with the latest laparoscopic simulator in a 360° surrounding. Participants were exhilarated by the high level of immersion. The setup enables a completely new generation of surgical training.